Sifat Mekanis & Struktur Mikro Aluminium Paduan (Al-Si) Pada Pengecoran Dengan Menggunakan Cetakan Berputar - Uswatul Hasanah Mihdar; Ahmad Nurul Muttaqin (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
This study aims to analyze the effect of variations in mold rotation speed and pouring temperature on the quality of casting aluminum alloy (Al-Si) which includes mechanical properties and microstructure. The selected speed variations are 200 rpm, 250 rpm, and 300 rpm. While the pouring temperature variations are 640oC, 660 oC, and 680 oC. The tests carried out were the hardness test and tensile test as well as a photo of the structure micro to be used to calculate the average grain size. The highest hardness value is found at 300 rpm with a temperature of 680 oC of 81.42 HB, while the lowest hardness value is found at 200 rpm with a temperature of 640 oC of 77.9 HB. The highest tensile strength is found at 300 rpm with a temperature of 660 oC 236.52 N/mm2 and the lowest tensile strength is at 250 rotations with a temperature of 680 of 171.92 N/mm2. The lowest average grain size value is found at 300 rpm rotation with a temperature of 680oC of 87.1781 Âµm, while the highest average grain size value is found at 200 rpm rotation with a temperature of 640 oC of 139.951 Âµm.